Mobile application for field knowledge data of urban river catchment decision support system - Usman F.; Omar R.C.; Sidek L.M. (Newswood Limited, 2023)
Water quality monitoring in urban area is a must. Regard to development and increasing of population due to urbanization, it has catapulting degradation effect to water quality of river. River Penchala is one of main river in Klang basin flows crossing urban area where diverse land use established. From historical data on its water quality, River Penchala was facing very polluted water with Water Quality Index range from III to V. Data on water quality periodically collected from several measurement stations along this river but analysis and interpretation of those information require appropriate strategy to implement the correct technique and/or procedure in order to improve the water quality of the river. This paper present development of mobile application for field knowledge data collection to be used by a decision support system. Previous methods on development of water quality decision support system are also discussed. At the end of this paper an initial framework of decision support system for River Penchala river catchment will be presented.